Smart Electric Energy Consumption Monitoring System Using IoT - ORPHOMMA, Sounith; SOUKHAVONG, Sengthong; SOUVANNALITH , Chanhpheng; NANTHAVONG, Bounphong (Souphanouvong University Journal Multidisciplinary Research and Development, 2019)
This paper was developed a smart electric energy consumption monitoring system to use the PZEM-004T sensor module for the reader the current and voltage. Then sends to the Node MCU ESP8266 board to make a calculation and process to values such as current, voltage, power, energy and electric cost to display on the screen of LCD, smartphone by Blynk App and also send and record the parameters values on the website thingspeak; by benefiting from the advance in technology, information and internet of Things: IoT From the experimental results, the system can work as intended, displaying parameters in the graphs and number in the real time; also can detect the values in nowadays, previous and automatically record values. So, it was found that the system is developed. It is possible to use it or improve and develop to be smart meter in the future to use instead of the current meter system and can be used to track electrical values as needed which makes for a comfortable in monitoring electric energy usage in any time and help to be conscious for energy consumption to save on electricity.